If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -2 = 3 + 7x Reorder the terms: -2 + 8x = 3 + 7x Solving -2 + 8x = 3 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -2 + 8x + -7x = 3 + 7x + -7x Combine like terms: 8x + -7x = 1x -2 + 1x = 3 + 7x + -7x Combine like terms: 7x + -7x = 0 -2 + 1x = 3 + 0 -2 + 1x = 3 Add '2' to each side of the equation. -2 + 2 + 1x = 3 + 2 Combine like terms: -2 + 2 = 0 0 + 1x = 3 + 2 1x = 3 + 2 Combine like terms: 3 + 2 = 5 1x = 5 Divide each side by '1'. x = 5 Simplifying x = 5
| 6x+20=137 | | -5(t-3)-7(-3t-8)=15(t+3)-4 | | 13/9=x/18 | | F(4)=4*4+5 | | 2.89=0.86b | | (2x^2-4x)(x-2)=0 | | 26-3w=5 | | -4(z-1)=-5z | | 1/100000000 | | (3x+2y^2)ydx+2(2x+3y^2)xdy=0 | | 2(3x-5)=-58 | | F(3)=4*3+5 | | 2a-3b+5a+6b= | | 0.8+5=.02(40-x) | | 20*4/5 | | y-3=(1/4)(x-5) | | 4x=8x-10 | | f(2)=4*2+5 | | 2q+373=811 | | 10-8x=4x | | 3(x+3)=2(3+x) | | y-3=1/4(x-5) | | 2:3x-5=4x-1:6 | | Ln(x^2-1)-ln(x+1)=1 | | 2q+433=921 | | X+44+2x-6=180 | | -6z+10=-5z | | 4j+8=3j | | (2x-5y+6)-(4x-3y+7)= | | 23x-5=4x-16 | | 2x+12x=4x-10 | | -3k+1-3k=19 |